Epilepsy Board Review : A Comprehensive Guide - Koubeissi, Mohamad Z.; Azar, Nabil J. (Springer New York : Imprint: Springer, 2017)
This concise text mirrors the content of the Epilepsy Board as distributed by the American Board of Psychiatry and Neurology. Epilepsy diagnosis, classification and treatment are thoroughly covered, along with seizure classification, epidemiology, normal and abnormal EEG, and treatment with antiepileptic medications and other modalities. Formatted with multiple choice questions and explanations, this complete resource will prepare physicians and students for the Epilepsy Board examination and provide the latest clinical approaches.- Resumé vydavatel